Enhancing Pre‐Service Teachers' Understanding of Quadrilaterals Through Wiki‐Supported Collaborative Learning. - Duatepe‐Paksu, Asuman (Journal of Computer Assisted Learning, 2026)
Background: Pre‐service mathematics teachers frequently struggle with understanding the definitions and hierarchical classifications of quadrilaterals, often misidentifying inclusive relationships. These misconceptions hinder their ability to teach geometry effectively and reflect gaps in both content knowledge and pedagogical readiness. While collaborative digital tools like wikis have demonstrated potential for fostering reflective and dialogic learning, their application in mathematics teacher education remains limited and underexplored. Objectives: This study aimed to investigate how a wiki‐based collaborative learning environment could enhance pre‐service teachers' conceptual understanding of quadrilaterals and inform the development of evidence‐based instructional design principles. Methods: This study adopted a three‐phase Design‐Based Research (DBR) methodology, comprising a pilot study and two iterative cycles, with 31 pre‐service mathematics teachers participating (4 pilot, 8 Iteration 1, 19 Iteration 2). The intervention used a Moodle‐based wiki in which participants collaboratively defined six quadrilaterals and determined instructional sequencing. Each phase involved designing wiki scaffolds, implementing the task, and analysing weekly wiki logs and interaction patterns to inform iterative refinements to task structure and scaffolding. Improvements were made on task design and scaffolding strategies between cycles considering wiki content analysis. Results and Conclusions: Findings indicate that wiki‐supported collaboration progressively enhanced participants' definitional precision, engagement in hierarchical reasoning, and pedagogical content knowledge. Over time, learners shifted from exclusive to inclusive definitions, demonstrating advancement along van Hiele levels of geometric thinking. Despite persistent challenges such as uneven participation and limited multimodal representation, the study confirms the potential of wikis as social constructivist tools in teacher education and contributes practical design principles for integrating collaborative technologies into mathematics instruction. Practitioner Notes /Lay Summary: What is currently known about this topic? Pre‐service teachers often misclassify quadrilaterals and their properties.Understanding inclusive definitions indicates advancement in van Hiele's geometry model.Wikis can support collaborative learning but are underused in mathematics.Effective wiki use requires scaffolding, structure, and peer engagement.What does this paper add? Shows how wiki tasks improve quadrilateral knowledge among pre‐service teachers.Demonstrates a shift from exclusive to inclusive definitions across iterations.Identifies persistent challenges such as uneven participation in collaboration.Provides empirically grounded design principles for wiki use in teacher training.Implications for practice/policy Teacher education should integrate structured wiki‐based collaborative activities.Clear scaffolds and role expectations are vital for productive peer interaction.Wikis can help future teachers connect content knowledge with pedagogy.Policy should promote digital collaboration tools in mathematics teacher training.